Sentencing Disparities in Corruption Cases and Judicial Discretion in Indonesian Courts - Daulay, Ahmad Fadli (PPPM, Sekolah Tinggi Ilmu Hukum (STIH) Biak-Papua, 2025)
Judicial discretion in case adjudication often leads to sentencing disparities, including in cases of corruption. This phenomenon is evident in Decision Number 77/Pid.Sus-Tpk/2023/PN.Jkt. Pst and Decision Number 92/Pid.Sus-Tpk/2023/PN Mks. This study explores the factors contributing to sentencing disparities and the judicial considerations in these decisions. The research employs a normative juridical approach. The findings indicate that sentencing disparities are influenced by the Continental European legal system adopted by Indonesia, which does not emphasize the use of precedent; the broad discretion granted to judges; the lack of standardized sentencing guidelines; and personal factors inherent to judges. In both cases, disparities arose due to differing judicial perspectives on the purposes of sentencing, as well as the defendants’ confessions and personal circumstances, which were taken into account. These findings highlight the complexities involved in achieving justice in corruption cases.